RECENT CHANGES IN PRODUCING OF THE INTERMEDIATE WATER IN THE OKHOTSK SEA AND ITS PROPERTIES - Y. I. Zuenko; A. L. Figurkin; V. I. Matveev (Известия ТИНРО, 2018)
Data of long-term observations on the cold intrusions in the warm intermediate layer of the Okhotsk Sea are overviewed, considering these intrusions as fresh portions of the Intermediate water of local origin. They are formed in the process of the high-density Bottom Shelf water cascading from the northwestern shelf, mainly in the submarine canyon at northwestern Sakhalin. Transport of these new-formed portions is traced in the flows of cyclonic circulation of the Okhotsk Sea waters from the area of their origin to the southern Kuril Straits, that takes from 2 to 6 years. Similar intrusions are found in the Pacific, mainly at southern Kuril Islands, where they penetrate presumably through the Vries and Bussol Straits. Year-to-year variability of the Bottom Shelf water and the new-formed Intermediate water properties are analyzed in dependence on external factors. There is determined that the volume and density of the Bottom Shelf water depend on winter severity that could be quantitatively explained by the ice cover; all these parameters decrease recently. Salinity of the new-formed Intermediate water has similar changes. Besides, tidal mixing influences on its salinity, in particularly at the Kuril Straits, so the tidal 18.6-year cycle is presented in the salinity variations. On the contrary, variations of the minimal temperature in the cold-water lenses of the fresh Intermediate water of local origin do not correlate with the changes in their production because of auto-compensatory effect for temperature in the process of its cascading to different depths. The same effect is obviously applied to dissolved oxygen, that’s why the oxygen content in the upper intermediate layer at the area of cascading is rather stable and doesn’t correlate with the ice cover changes. However, ventilation of the medium and deeper parts of the intermediate layer decreases on the background of recent lowering of the Intermediate water producing, in particularly the production of the water with σq ≥ 26.8. On a distance from the area of cascading, the tendency to deoxygenizing spreads over the whole intermediate layer of the Okhotsk Sea.